FLUXES OF ENERGY, WATER AND CO2 ABOVE A TROPICAL MONSOON FOREST IN DONG NAI: RESULTS OF 10 YEARS OF MEASUREMENTS - Ju. A., Kurbatova; O. A., Kuricheva; V. K., Avilov; Dinh, Ba Duy; Vu, Manh; Nguyen, Van Thinh; DO, Phong Luu; N. A., Myslitskaya (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
This paper explores more than 10-year continuous measurements of energy, water and carbon dioxide fluxes on a first-established eddy covariance site in Vietnam above a mature semi-evergreen tropical seasonal forest. Daily, seasonal and interannual variations of turbulent fluxes and meteorological parameters were studied. Evapotranspiration decreased in the second half of a dry season and net ecosystem exchange of CO2 increased to positive values (the tropical forest becomes a source of CO2 instead of a sink) in a hot-dry period of a year (March-May). Net radiation was the parameter with minor interannual and seasonal variation. Precipitation varied significantly from year to year and the variation was great between dry seasons. Variations of precipitation affected the annual rate of evapotranspiration but had no proven effect on the annual net ecosystem exchange of CO2. The ecosystem of tropical forest was the considerable net sink of CO2 from the atmosphere.